The Influence of Service Quality Factors and Perceived Risk on Purchase Intention through Online Platforms of Customers in Bangkok and its Metropolitan Area - ชลาลัย, กฤษดา; พับขุนทด, กุลธิดา; โทดา, เสฎฐพัตน์; ประทุมเมือง, รัชตา; ลัดหนองขี, บุญอนันต์; ศรีติสาร, ฐาปานีย์; Srimuang, Wipada (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The objectives of this research were to study: 1) the importance of e-commerce service quality factors affecting purchase intention on online platforms, 2) the significance of perceived risk influencing purchase intention on online platforms, 3) the level of purchase intention on online platforms, and 4) the influence of e-commerce service quality factors and perceived risk on purchase intention among customers in Bangkok and its metropolitan areas. This study employed a quantitative research methodology, utilizing a questionnaire as the primary research instrument. The sample consisted of 400 individuals who had previously purchased products through online platforms and resided in Bangkok and its surrounding areas. The statistical tools used for data analysis included frequency, percentage, mean, standard deviation, and multiple regression analysis.The research findings indicated that e-commerce service quality factors significantly influenced online purchase intention at a high level, with platform efficiency identified as the most critical factor. Similarly, perceived risk was also found to be at a high level, with performance risk being the most crucial factor. Additionally, purchase intention on online platforms was reported at a high level. Hypothesis testing revealed that the key service quality factors influencing purchase intention included: 1) efficiency, 2) responsiveness, and 3) privacy. Regarding perceived risk factors, the influential aspects were: 1) security risk, 2) performance risk, 3) financial risk, 4) social risk, and 5) psychological risk, all of which were statistically significant at the 0.05 level.